PENGARUH PENGAWASAN, KOMITMEN PEGAWAI DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI DINAS PERDAGANGAN DAN PERINDUSTRIAN KOTA TANJUNGBALAI - Rima Wulandari; Suwito .; Zulfitri Syawaluddin Hasibuan; Evan Botung Daulay; Adi Kuncoro (Jurnal Prodi Fakultas Ekonomi-UISU, 2021)
The formulation of the problem in this study are: How do supervision, employee commitment and work environment influence employee work productivity. This study aims to examine how the influence of supervision, employee commitment and work environment on employee work productivity. With total sampling technique, the sample in this study amounted to 35 people. Supervision variables partially have a positive effect on employee work productivity. Employee commitment variable partially has a positive effect on employee work productivity. Work environment variables partially have a positive effect on employee work productivity. Supervision variables, employee commitment and work environment simultaneously have a positive and significant effect on employee work productivity.